Frequency of Hypocalcemia in Neonates with Hypoxic Ischemic Encephalopathy Presenting Nursery Unit of Saidu Group of Teaching Hospital - Ullah, Irfan; Khan, Sardar; Waqas, Muhammed; Alam, Shahab (Biological and Clinical Sciences Research Journal, 2025)
Hypoxic-ischemic encephalopathy (HIE) is a major cause of neonatal morbidity and mortality. Metabolic disturbances, including hypocalcaemia, are frequently observed in neonates with HIE and may worsen neurological outcomes if not promptly identified and managed. Early detection of hypocalcaemia is therefore essential in neonatal intensive care settings. Objective: To determine the frequency of hypocalcaemia in neonates with hypoxic-ischemic encephalopathy presenting to the nursery unit of Saidu Group of Teaching Hospital. Methods: This cross-sectional study was conducted in the Paediatric Unit of Saidu Group of Teaching Hospital from 12-01-2025 to 12-04-2025 and included 134 neonates aged 1–25 days diagnosed with hypoxic-ischemic encephalopathy. HIE was defined based on Apgar scores below 5 at 1 and 5 minutes, need for resuscitation at birth, presence of seizures, altered level of consciousness, and neuroimaging findings consistent with encephalopathy. Hypocalcaemia was defined as ionized calcium levels <4.4 mg/dL. Data were analyzed using SPSS version 21. Associations between hypocalcaemia and demographic or clinical variables were assessed, with a p-value <0.05 considered statistically significant. Results: Among 134 neonates, 86 (64.2%) were male and 48 (35.8%) were female. The mean age was 6.76 ± 6.48 days. The mean ionized calcium level was 4.55 ± 0.48 mg/dL. Hypocalcaemia was observed in 42 neonates (31.3%). A statistically significant association was found between hypocalcaemia and younger age (1–5 days) (p = 0.001). No significant associations were observed with gender, socioeconomic status, place of residence, or birth weight categories (all p > 0.05). Conclusion: The frequency of hypocalcaemia among neonates with hypoxic-ischemic encephalopathy was 31.3%. Neonates aged 1–5 days were at significantly higher risk. Routine monitoring of serum calcium levels in the early neonatal period is recommended to detect and manage hypocalcaemia in infants with HIE.